Analisis Perilaku Komunikasi Anggota Komunitas Meme Comic Indonesia Di Facebook - Aditya, Ikhlash; Sucipta, Johantan Alfando Wikandana (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This research is motivated by the proliferation of memes, which have become a new trend in communication on social media, including Facebook. Meme Comic Indonesia (MCI) is one of the popular Facebook groups for sharing memes, with its members consisting of hundreds of thousands of individuals from various regions. The aim of this research is to analyze the communication behavior of meme-sharing among the members of the Meme Comic Indonesia group on Facebook. The study employs a qualitative approach with data collection techniques such as observation, interviews, and documentation. The theoretical framework used in this research is the theory of symbolic interactionism, which comprises three main concepts: mind, self, and society. The results of the research indicate that, in the mind concept, group members share relatively similar motivations and thought patterns in interpreting and using memes as a means of self-expression and entertainment. In the self concept, members shape their online identities and self-images through shared memes to gain acceptance within their Facebook community. In the society concept, simultaneous interactions among Facebook members contribute to a shared understanding of evolving memes over time. The communication behavior of Meme Comic Indonesia group members includes interactions through comments, likes, and the exchange of information through memes. Social interactions among group members in interpreting memes contribute to a shared understanding that can evolve with the passage of time..